WORKFORCE DIVERSITY AS A STRATEGIC DRIVER OF ACADEMIC PERFORMANCE: EMPIRICAL EVIDENCE FROM MALAYSIAN PRIVATE UNIVERSITIES - Khushairi, Noor Azreen Mohd; Sabri, Sabiroh Md; Ismail, Ismalaili; Shafee, Mohd Imran Khusairi; Hamid, Hamidey (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
To thrive in today’s intensely competitive education market, private colleges rely greatly on the qualities of their faculty. While a diverse workforce is widely regarded as a strategic advantage, recent research on how this influences employee performance in higher education has yielded varied results. Our study investigates how specific diversity factors such as age, gender, ethnicity, and educational background influence academic performance in Malaysian private colleges. We also wanted to investigate if the organization’s entire culture can assist bridge the gap between diversity and performance. After polling 175 academic staff members in the Klang Valley and processing the figures via structural equation modelling, the results were clear: every single diversity aspect we considered improved performance significantly. When academics work with colleagues from different backgrounds, they naturally share a wider range of knowledge, collaborate better, and introduce fresh ideas. Interestingly, while a solid organizational culture directly elevates employee performance, it does not actually change the way diversity itself impacts that performance. Ultimately, our findings make a strong case for university leaders to treat workforce diversity as a key driver of their institution’s success, rather than just a demographic checkbox.